2019
DOI: 10.3946/kjme.2019.143
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gender and coping mechanisms with burnout events in first-year medical students

Abstract: First-year students are susceptible to experiencing burnout if the coping mechanism being used is inadequate; therefore, employing effective coping mechanisms could help students to minimize burnout. Coping mechanisms are divided into five groups: problem-focused, emotion-focused, dysfunctional coping, adaptive, and maladaptive coping. The burnout dimension includes emotional exhaustion, cynicism, and decreased academic performance that may be influenced by gender. This study aims to elaborate on the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
3
14
0
2
Order By: Relevance
“…Regarding the relationship between coping and burnout, the meta-analysis of Shin et al (2014) revealed that problem-focused coping correlates negatively with the three dimensions of burnout symptoms, whereas emotion-focused coping correlate positively with the three dimensions. More recently, Palupi and Findyartini (2019), using four coping strategies, also find that more negative coping strategies show a positive correlation with emotional exhaustion and depersonalization, whereas more positive coping strategies have a negative correlation only with depersonalization.…”
Section: Stress and Copingmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the relationship between coping and burnout, the meta-analysis of Shin et al (2014) revealed that problem-focused coping correlates negatively with the three dimensions of burnout symptoms, whereas emotion-focused coping correlate positively with the three dimensions. More recently, Palupi and Findyartini (2019), using four coping strategies, also find that more negative coping strategies show a positive correlation with emotional exhaustion and depersonalization, whereas more positive coping strategies have a negative correlation only with depersonalization.…”
Section: Stress and Copingmentioning
confidence: 94%
“…Lazarus (1999) distinguishes between problem-focused coping and emotion-focused coping. Similarly, other authors also propose a dichotomous classification that differentiates between positive and negative coping strategies (Palupi & Findyartini, 2019). Positive, problem, or behavioural coping can be defined as rational strategies oriented to solve the problem or control the situation.…”
Section: Stress and Copingmentioning
confidence: 99%
“…However, based on Table 2, male teachers have felt more emotionally exhausted than female teachers due to COVID -19. This result challenged the common findings of several studies showing that females tend to feel more emotionally exhausted than males (Alonso et al, 2020;Marchand et al, 2018;Palupi & Findyartini, 2019). A popular notion probably because male teachers do the heavy physical work at school carrying and delivering the learning modules to students.…”
Section: Resultsmentioning
confidence: 56%
“…Actually, study regarding gender composition and place of residence among medical students in Indonesia is limited. In other aspect regarding this topic, Palupi and Findyartini [13] conducted a study about the relationship between gender and coping mechanisms with burnout events in first-year medical students and their result was adaptive coping had a positive correlation with perception of personal accomplishment. From their perspective, adopting an appropriate coping mechanism may help students to minimize the negative side effect of tough and very demanding medical education.…”
Section: Resultsmentioning
confidence: 99%